Anesthesia with propofol‐remifentanil combined with rocuronium for bronchial foreign body removal in children: Experience of 2 886 cases. Issue 1 (11th May 2018) - Qiu, Yongsheng; Qu, Jinrong; Li, Xiang; Li, Hailiang
Abstract: Importance: The appropriate anesthetic method can reduce the complications of children with tracheal foreign body and reduce the mortality rate of children. What kind of anesthetic method to choose has always been the focus of debate Purpose: To evaluate the efficacy and safety of anesthesia with propofolremifentanil combined with rocuronium for foreign body aspiration (FBA) removal with the positive‐pressure ventilation technique. Methods: Medical records of patients who underwent bronchoscopy for evaluation of FBA in our unit from January 2015 to January 2018 were retrospectively reviewed. Demographic data (age and sex), nature of foreign body and location, complications, length of hospital stay and outcome were analyzed. Results: A total of 2 886 children were included in this study. The median age was 24 months (8 months to 10 years). FBA was detected and removed in 95.6% of patients. The average operation time was 17 ± 5 min and average length of hospital stay was 2 days. Observed peri‐interventional complications included desaturation (n = 66), laryngospasm (n = 19), laryngeal or subglottic edema (n = 15), irritating cough (n = 3), body movement (n = 76) and pneumonia (n = 206). No deaths occurred during hospitalization or follow‐up in this series. Interpretation: Anesthesia with propofol‐remifentanil combined with rocuronium under positive‐pressure ventilation is an effective and safe technique during FBA removal in children.